EFFECT OF THE MONOMERS ADDITION RATE AND INITIATOR CONCENTRATION IN THE SYNTHESIS OF MESOPOROUS POLYSTYRENE NANOPARTICLES BY SEMICONTINUOUS HETEROPHASE POLYMERIZATION - Puca P., M. (2012)
The technique named semicontinousheterophase polymerization was used to synthesize mesoporous polystyrene nanoparticles. The developed process was under monomer-starved conditions which monomer was continously added to the reactor containing an aqueous solution of emusifier and initiator. The effects of the rate of organic mixture addition and concentration of initiator on kinetic behavior, the particle size, pore diameter and porosity were studied.The results obtained were as follows: the conversions were near to 95% (≈ 20% content of solids), with particle size between 15 and 30 nm with low polydispersity, pores size between 4 and 6 nm and porosity between 10 and 30%. According to the results’ statistical analysis, the conversion, the particle and pore size depend directly on the rate of the organic mixture addition and not on the concentration of initiator. On the other hand, the porosity is directly proportional to the rate of organic mixture addition and inversely proportional to the concentration of initiator.